“Dancing belly” in an old diabetic lady - Dubey, Souvik (J Family Med Prim Care, 2020)
Movement disorder, although rare, is increasingly being recognized as the initial presenting sign of the hyperglycemic state. Although chorea-ballism has frequently been reported among diabetics, monoballism is a very rare phenomenon. While myoclonus is common, diaphragmatic myoclonus is extremely rare. Moreover, diaphragmatic myoclonus as the initial presenting manifestation has never been reported before. Herein, we report an index case of a 62-year-old previously undiagnosed diabetic lady presented with acute onset constellation of multiple abnormal movements viz. monoballism, focal myoclonus, action myoclonus, and diaphragmatic myoclonus. All of them disappeared with achieving normoglycemia. This case underscores the importance of rapid capillary blood glucose testing in any patient presenting with acute onset abnormal movements. This approach can especially be rewarding as it helps in the rapid diagnosis of a reversible catastrophe and avoiding unnecessary costly investigations.